Stigma, Taboo, and Public Health: A Sociological and Bioecological Approach to the Use of Performance and Image-Enhancing Drugs - Coutinho, Luis Felipe Duarte; Nascimento-Salgado, Leonardo Vaz; Monteiro-Bontempo, Valentina; Martins-Chaves, Roberta Rayra (Advances in Social Sciences Research Journal, 2025)
Background: This article provides an interdisciplinary review of performance-enhancing and image-enhancing drugs (PEDs) through sociological and bioecological lenses. The analysis reveals a growing and complex trend of PED use among recreational users. Methods: Utilizing Bronfenbrenner’s bioecological theory along with covering books, reports, anti-doping notes, observational studies and systematic reviews, this review explores how different pressures influence PED use. Goffman’s concept of stigma highlights the marginalization PED users encounter, as they are often associated with cheating or health risks. Findings: The article examines how different systems spread unrealistic body ideals, which intensifies pressures on individuals to normalize PED use. The western cultural dynamic connects PED use to both physical aspirations and deeper self-worth issues related to body image and it is the duty of healthcare professionals not only to refuse such prescriptions but also to actively engage in prevention and public awareness efforts regarding the dangers of PEDs. Interpretation: Emphasizing the need for an empathetic yet firm medical approach, the article advocates for healthcare professionals to engage openly with PED users to foster supportive dialogues with. Such engagement is crucial for effective public health interventions that can address both the physical and psychological risks of PED use, ultimately contributing to a more health-centered societal perspective on performance and body image. In conclusion, this article emphasizes the urgent need to reframe the conversation around PEDs, recognizing their complex social underpinnings to better approach affected individuals.